The value of secondary forest patches for bird conservation in palm oil landscapes of Riau, Sumatra - ERNIWATI ERNIWATI; ERVIZAL AMIR MUHAMMAD ZUHUD; YANTO SANTOSA; ISWANDI ANAS (Biodiversitas Journal of Biological Diversity, 2016)
Erniwati, Zuhud E, Santosa Y, Anas I. 2016. The value of secondary forest patches for bird conservation in palm oil landscapes of Riau, Sumatra. Biodiversitas 17: 791-798. Land use change due to palm oil expansion is considered to be one of the key drivers of biodiversity loss in the tropics, particularly in Indonesia, which is the biggest producer of palm oil in the world. In the last three decades, large scale plantations and smallholdings of palm oil have come to dominate the agricultural landscape, leaving small secondary forest patches surrounded by plantations. We currently have only limited current knowledge about the value of secondary forest patches for bird conservation in the palm oil landscape. The aim of this study was to contribute to our understanding of the value of remnant forest patches, smallholdings, and large scale plantations for bird conservation in the palm oil plantation landscape. We also examined the influence of the age of the palm oil plantations on bird diversity. We conducted the survey from March to April 2016. We surveyed 40 line transects in palm oil landscape in Riau Province, eight transects in secondary forest patches, 16 transects in smallholdings and 16 in a large scale plantation. Seventy three bird species, 41families and 1579 individuals were recorded; 16 species being protected in all sites. Our result showed that secondary forest has higher bird diversity than the palm oil plantations; large scale plantation support higher bird species abundance than smallholdings, while old age stands (>19 year) have higher species abundance within large scalepalm oil plantation. An important management implication arising out of our results is that preserving natural forest patches in a landscape dominated by palm oil plantations is one of the strategies to conserve avifauna diversity.